Airborne Fungi in Wood and Wood Based Board Factories - Sivrikaya, Hüseyin; Kara, Oemer; Sivrikaya, Hüseyin (Sage Publications Ltd, 2009)
This study was a comparative investigation of the isolation and identification of airborne fungi between wood processing and melamine coated board processing factories. Isolation of airborne fungi was performed in four small sized enterprises engaged in wood processing and melamine coated board processing, located in the West Black Sea region of Turkey. Petri dishes containing Rose-Bengal streptomycin agar were exposed to air in the plants for 15 minutes. The highest fungal colony counts were observed in plant D, where the average value was 72 cfu per plate. Penicillium was the most widespread species identified in all the plants. Aspergillus fumigatus, which has major importance among the airborne fungi because it can cause health problems for workers, was only isolated in plant A.
Keywords: Airborne Fungi; Wood; Melamine Coated Board; Penicillium; Aspergillus